METABOLIC EFFECTS OF TULBAGHIA VIOLACEA HARV. IN A DIABETIC MODEL. - Moodley, Kogi; Mackraj, Irene (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Diabetes mellitus (DM) is a cluster of metabolic diseases with chronic hyperglycemia as a defining feature, associatedwith long-term organ damage and dysfunction. In this study we examined the effect of Tulbaghia violacea rhizome methanolicextract on blood glucose and lipids in normal and streptozotocin-induced diabetic rats.Materials and Methods: Male Wistar rats (250-300g) were injected intraperitoneally (i.p.) with streptozotocin (60mg/kg bodyweight) to induce diabetes; or provided with distilled water for the control (CON) (3 ml/kg/b.w.) animals and treatment with TVL(60mg/kg.b.w). The rats were divided into 5 groups of 6 animals per group as follows: Non-diabetic control (NDC)-receiveddistilled water (3ml/kg.b.w), Non-diabetic TVL (ND+TVL)-received TVL (60mh/kg b.w), Diabetic control (DC)-received distilledwater (3ml/kg.b.w), Diabetic experimental (D+TVL)-received TVL (60mg/kg.b.w), Diabetic experimental (D+M)-receivedMetformin (250 mg/kg.b.w). All doses were administered daily via oral gavage.Results: TVL-treated animals showed reduced blood glucose, increased plasma insulin, reduced plasma TG, TC, VLDL andincreased HDL. Furthermore we found decreased thiobarbituric acid reactive substances (TBARS) and increased superoxidedismutase (SOD) activity and nitric oxide significantly. Regarding renal parameters we found increased blood urea nitrogen (BUN),and improved renal morphology in TVL-treated animals.Conclusion: Tulbaghia violacea has a hypoglycaemic effect which could due to its effects on multiple pathways of thehyperglycemic process. Further work is needed to identify the mechanism of its antidiabetic effect.